Assessing accounting for citizenship: an empirical analysis of the corporate control and capital structure decisions. (1st January 2014) - Segura, Liliane Cristina; Abreu, Rute; Filho, Marco Antonio Figueiredo Milani
The accounting for citizenship pursues the citizen's best interest to protect their future financial well-being, in order to adjust the corporation control pressure through capital structure decisions that aim to promote sustainable practices and to improve the corporate governance. Studies of corporate governance identify that lenders now consider the cost of capital and the influence of the concentration of capital in the financial decisions. This article presents a synopsis of corporate control based on several authors and determinants of capital structure. The empirical part develops a longitudinal exploratory analysis from 356 corporations included from 2004 to 2009. The dependent variable used is debt (long-term, short-term, financial and total debt) and the independent variables are concentrated control and significant influence. Several control variables are used to avoid bias in the analysis. The results show that corporate control could change, in convergence and divergence, the capital structure decisions.